Effects of Thai Plant Extracts on the Oriental Fruit Fly1 III. Attractancy Test - Sutharm Areekul; Prateungsri Sinchaisri; Saen Tigvatananon (Agriculture and Natural Resources, 1988)
Attractive potency tests were made on 487 extracts of 231 kinds of plants among which 205 were identified and 26 were unknown species. The rates of competitive attractiveness were determind from the number of the Oriental fruit fly, Dacus dorsalis Hendel, which entered at 1, 6, 12 and 24 hours in to traps in an olfactometer in which one gm equivalent of each plant extract was placed in each trap. Eight day old flies of both sexes were used in this experiment. Plants among which demonstrated highly attractive to the test flies were Crinum asiaticum Linn., Dieffenbachia requine Schott., Nerium indicum Mill., Ocimum sactum Linn., Thitonia diversifolia Gray, and Vallaris graba Ktze. Plants among which their extracts exhibited moderate attractive potency were Bixa orellana Linn., Curcuma comosa Roxb., Cymbopogon flexuosus Nee & Stend., Datura metel Linn., Elsholtzia blanda Benth., Holmoskioldia sanguine Retz., Homalomena sp., Lantana camara Linn., Melia azederach Linn., Momorica charantia Linn., Monstera deliciosa Liebm., Murraya paniculate Jack, Musa sapientum Linn., Nerium indicum Mill., Ocimum gratissimum Linn., Poinciana pulcherima Sw., Quisquallis indica Linn., Ruellia tuberose Linn., Terminalia catappa Linn., Thysanolaena maxima Kty., and Vallaris glaba Ktze. Among unidentified plants, Chang-Kan, En-Luang, and Kha-pa were included in this case.